2016
DOI: 10.1016/j.pdpdt.2015.07.169
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial 5-ALA photodynamic therapy and glioblastoma: Preclinical model development and preliminary results

Abstract: We have developed a reproducible and reliable rodent model for interstitial 5-ALA PDT. We found that the effects of 5-ALA-PDT are dependent on light delivery conditions. Although the low-fluence-rate treatment was better tolerated, 5-ALA-PDT induced more necrosis using fractionated delivery at a high fluence rate. These results require confirmation with further studies involving larger populations and additional fractionation schemes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 43 publications
(74 reference statements)
3
33
0
Order By: Relevance
“…Therefore, our observation that PDT is able to induce necrosis in glioblastoma cells in vitro is quite unique and translates perfectly with in vivo observations showing important necrosis in treated tumors [23].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Therefore, our observation that PDT is able to induce necrosis in glioblastoma cells in vitro is quite unique and translates perfectly with in vivo observations showing important necrosis in treated tumors [23].…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, PDT is known to induce both necrosis and apoptosis in glioblastoma [19,20]. Recently, Receptor Interacting Protein kinase 3 (RIP3), a key protein of the programmed necrosis pathway (necroptosis) was demonstrated to be involved in PDT-induced glioblastoma cell death induced by PDT [21][22][23] and other cell death inducers [24][25][26]. The current model of necroptosis relies on the assembly of the "necrosome" complex, in which Receptor Interacting Protein kinase 3 (RIP3) interacts with RIP1, Fas-Associated protein with Death Domain (FADD) and Caspase-8 upon a combined treatment of TNF-α, Smac-mimetic and pan-caspases inhibitors [27].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the application of brain hypothermia is an established procedure in neurology . Apart from applying 100% oxygen breathing during PDT, it may be important to exploit preclinical observations of an improved tumor tissue response to PDT by fractionated irradiation . How tumor tissue phototoxicity might be enhanced by simply interrupting irradiation a few times for a few minutes only can be understood when looking at oxygen diffusion between capillaries during irradiation, resulting in a relative depletion of oxygen available for the cells furthest away from the next capillary .…”
Section: ‐Ala Based Photodynamic Therapy Of Malignant Gliomamentioning
confidence: 99%
“…Fractionation (i.e., alternating the on/off period of light) might address this issue . Accordingly, Tétard et al previously reported data suggesting an improvement in the PDT effect after fractionated PDT compared with continuous illumination .…”
Section: Introductionmentioning
confidence: 99%